The results of magnetic separation use in ore processing of metalliferous raw basalt of Volyn region - Malanchuk, E.; Malanchuk, Z.; Korniienko, V.; Gromachenko, S. (Розробка родовищ, 2016)
Purpose. To determine the effectiveness of the electric field use in ore processing for extraction of native copper concentrate from raw basalt, to identify the most technologically advanced grain-size classes of the feed stock. To define the nature of the relationship between the amount of recoverable concentrate and the main dominant factors – separator field density and the coarseness of the prepared raw material. Methods. We used the substantiated physical and chemical methods of elemental, mineral, fractional, particle size distribution analysis of the basalt rock mass under processing, methods of laboratory, semi-industrial and industrial research into crushing, grinding, classification, and electromagnetic separation processes at the stages of ore preparation of raw materials for the production of metalliferous industrial products. The methods of statistical modeling and experimental results regression analysis have been applied. Findings. The preferred grain-size classes in the process of ore preparation and classification of basalt rock components for electrostatic separation were determined. The dependences of copper concentrate production from basalt, tuff and lava-breccia on the electrostatic field density while changing grain-size classes in the initial product were worked out. The regression dependences of the copper concentrate output on various relationships between grain-size classes in the initial material and the electric field density were obtained. Originality. The content of native copper in basalt, lava breccia and tuff was established and the preferred grain-size classes in the process of ore preparation were identified. It is for the first time that the magnetic susceptibility of all three components of basalt raw material was determined, and the influence of the magnetic field on the output of titano-magnetite concentrate was shown as well as the rational grain size of ore preparation was detrmined. The dependences of the copper concentrate output have been established and the efficien cy of the electrical separation in complex processing of basalt raw material has been proved.